Cross-quarter differential market reactions: An investigation of the audit effect hypothesis - LEE, Andrew (Institutional Knowledge at Singapore Management University, 2016)
The purpose of this paper is to investigate the audit effect hypothesis for the cross quarter differential market reactions to earnings announcements. Earnings response coefficients are focused upon as indicators of perceived earnings quality. The evidence suggests that investors of Singapore-listed companies respond more strongly to earnings announcements in the fourth quarter than other interim quarters. Finds support the notion that investors attach different degrees of reliability to interim quarter earnings relative to final quarter earnings. Findings in this study shed new light on the audit effect hypothesis and are relevant to accounting regulators and audit committee members seeking to enhance credibility of earnings announcements.